2004
DOI: 10.1128/jvi.78.17.9487-9498.2004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of AC2 and AC4 of Cassava Geminiviruses in Mediating Synergism and Suppression of Posttranscriptional Gene Silencing

Abstract: Posttranscriptional gene silencing (PTGS) in plants isPosttranscriptional gene silencing (PTGS) involves the degradation of viral and cellular mRNAs in a homology-dependent manner, and it is conserved in diverse eukaryotes (15,25). In plants, PTGS functions as a natural antiviral defense because plant viruses are both initiators and targets of PTGS (47). PTGS was first discovered in plants (30); however, a mechanistically similar phenomenon was later described in other organisms: it is called quelling in fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 303 publications
(229 citation statements)
references
References 61 publications
3
219
0
2
Order By: Relevance
“…Synergism between isolates of two cassava-infecting geminiviruses, ACMV and EACMV, has been observed and the genes mediating synergism have been identified (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004). Synergism between ACMV and East African cassava mosaic Cameroon virus (EACMCV) is a two-way process, as the presence of the DNA-A component of ACMV or EACMCV enhanced the accumulation of viral DNA of EACMCV and ACMV, respectively, in tobacco BY2 protoplasts (Vanitharani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synergism between isolates of two cassava-infecting geminiviruses, ACMV and EACMV, has been observed and the genes mediating synergism have been identified (Fondong et al, 2000;Pita et al, 2001;Vanitharani et al, 2004). Synergism between ACMV and East African cassava mosaic Cameroon virus (EACMCV) is a two-way process, as the presence of the DNA-A component of ACMV or EACMCV enhanced the accumulation of viral DNA of EACMCV and ACMV, respectively, in tobacco BY2 protoplasts (Vanitharani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Synergism between ACMV and East African cassava mosaic Cameroon virus (EACMCV) is a two-way process, as the presence of the DNA-A component of ACMV or EACMCV enhanced the accumulation of viral DNA of EACMCV and ACMV, respectively, in tobacco BY2 protoplasts (Vanitharani et al, 2004). ACMV AC4 and EACMCV AC2, the putative synergistic genes, are able to suppress post-transcriptional gene silencing (Vanitharani et al, 2004). In the present study, we demonstrated that NA and NB accumulation was Virulent pseudorecombination and synergism among ToLCVs also increased due to synergism, whilst the level of VA remained unchanged or decreased, indicating a unique asymmetric interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coding sequences of AC2 and AC4 genes from ACMV and EACMCV were fused to the cauliflower mosaic virus (CaMV) 35S promoter (35S) in a binary vector and introduced into Agrobacterium tumefaciens strain GV3101 as described in ref. 18. Transformation of Arabidopsis thaliana ecotype Columbia plants (Col-0) was performed by the floral dipping method (22).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we identified two types of virus-encoded PTGS-suppressor proteins: (i) the AC4 of African cassava mosaic virus Cameroon Strain (ACMV) and of Sri Lankan cassava mosaic virus (SLCMV) and (ii) the AC2 of East African cassava mosaic Cameroon virus (EACMCV) and of Indian cassava mosaic virus (ICMV). It is worth noting that not all AC4 proteins are PTGS suppressors (AC4ϩ), and that, for example, the AC4 of EACMCV (E-AC4) and ICMV are not PTGS suppressors (AC4Ϫ) (18). In addition, the AC2 of ACMV-Kenyan strain (A-AC2) and mungbean yellow mosaic virus and the C2 of tomato yellow leaf curl China virus were reported to possess silencing-suppression activity (19)(20)(21).…”
Section: Icrornas (Mirnas) Are Endogenous Small Noncodingmentioning
confidence: 99%